A phenomenological investigation into the use of therapist self-disclosure in compassion-focused therapy with forensic clients - Rachwal, Francesca (International journal of offender therapy and comparative criminology, 2024)
Existing research has demonstrated the benefits of therapist self-disclosure (TSD) in strengthening therapeutic alliance. However, little is known about its effectiveness in the forensic context. The current research sought to address this gap by interviewing six Compassion Focused (CFT) therapists who had experience of working across a range of forensic settings. Results of an Interpretative Phenomenological Analysis (IPA) indicated that all participants advocated using TSD as a powerful therapeutic tool when working with forensic clients. However, there was a tension between balancing risk with the rewards of TSD, and participants expressed how the secure forensic environment was not conducive to its use. There was a consensus that TSD was more strongly discouraged with clients who had sexual convictions. For some, this had an impact on their own disclosures. Training on the function of TSD is recommended in forensic practice to address some of the environmental barriers to its implementation.